Perlindungan Tenaga Kerja Anak - Kanyaka Prajnaparamita (Administrative Law and Governance Journal, 2018)
This study aims to determine the protection of child labor in Indonesia, especially the rules that protect child labor both in industrial areas and on entertainment such as artist child and the like. The research method used is legal research with statutory approach approach (analytical approach) which is analyzed with qualitative analysis. The results of the study show that child labor has gained enough protection from Indonesian legislation. Such protection is both at the level of the country's basic laws (contitutions) and the Law, as well as on derivative regulations issued by the central government, ministers, and local governments. Keywords: Labor Law, Child Labor, Child Protection